Назви головних весільних персонажів у буковинському діалекті / The names of the main members in the wedding Bukovinian dialect - Руснак Наталія; Руснак Юлія (Актуальні питання суспільних наук та історії медицини, 2014)
Rusnak Yulia, Rusnak Natalia. The names of the main members in the wedding Bukovinian dialect Slavic language kontitnuum gives ground to the analysis of the Bukovinian wedding terminology The article deals with the names of the main members of Bukovinian wedding. The origin of words is defined, together with their regional phonetic manifestations and distribution boundaries. Key words: Bukovinian patois, wedding rite vocabulary, a wedding term, nomination, periphrasis, appellation, desemantization. Rusnak Yulia, Rusnak Natalia. LA DÉNOMINATION DES PERSONNAGES PRINCIPAUX DU MARIAGE DANS LE DIALECTE DE LA BUCOVINE Les langues slaves sont devenus comme base pour l'analyse la terminologie de mariage de la bucovine. Dans cet article il s’agit de nominations des personnages de mariage secondaires dans le dialecte de bucovine. On a défini les origines des mots, leur phonétique leur manifestations dans différentes régions de l'Ukraine et les limites de leur distribution. Руснак Юлия, Руснак Наталия. НАЗВАНИЯ ГЛАВНЫХ СВАДЕБНЫХ ПЕРСОНАЖЕЙ В БУКОВИНСКОМ ДИАЛЕКТЕ Славянский языковой континуум стал основой для анализа буковинской свадебной терминологии. В статье рассматриваются названия главних чинов буковинской свадебной драмы. Проанализировано происхождение слов, их фонетические проявления в разных регионах Украины, границы распространения. Ключевые слова: буковинский диалект, лексика свадебной обрядности, свадебный термин, номинация, перифраза, апелятивации, десемантизация.